PERLINDUNGAN HUKUM TERHADAP ANAK LUAR KAWIN DALAM PEMBAGIAN WARIS ADAT TORAJA - Olivia Irianty Logo Tadu (University of Merdeka Malang, 2017)
The Decision of the Constitutional Court of the Republic of Indonesia Number 46 / PUU-VIII / 2010 has a positive impact on outsiders in demanding their rights to their biological father, the position of the child outside the marriage has only a civic relationship with the mother and the mother's family. Issued by the Constitutional Court Decision, the relationship of civility of children outside of marriage is not only related to mother and mother's family but with biological father and his father's family, Toraja's inheritance system has a fair system, if the outsider has no rights, demanding his right to his biological father, by deliberation but if the deliberation can not be resolved then it can be solved by the intervention of the Toraja adat chairman, if masi does not have a bright spot then the outsider can claim his rights in court, but in Adat Toaraja this community masi has a sense of kinship so that masi can be resolved, because if it has come to the village head or customary head then the family will be made into the ingredients of the local community.